Pengembangan Media Pembelajaran Kotak Belajar Ajaib (Kobela) Pada Materi Sumber Daya Alam Untuk Meningkatkan Minat Belajar Siswa Kelas IV SD Negeri 101961 Timbang Deli - Dina Kasputri; Layil Safitri; Emy Harianti (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This research was motivated by the low interest in learning of Class IV students at SD Negeri 101961 Timbang Deli and the lack of use of learning media. For this reason, teacher innovation is needed in designing learning. The use of learning media can create effective communication between teachers and students. The objectives of this research and development are 1) To determine the feasibility of the Magic Learning Box (Kobela) learning media in increasing the learning interest of Class IV Students at SD Negeri 101961 Timbang Deli. 2) To determine the effectiveness of the Magic Learning Box (Kobela) learning media in increasing the interest in learning of Class IV Students at SD Negeri 101961 Timbang Deli. The type of research used is research and development (Research and Development) using the ADDIE model (Analyze, Design, Develop, Implement and Evaluate). Data collection techniques use questionnaires, observation, interviews and documentation. The results of this research and development can be concluded that 1) The results of material expert validation obtained a score of 91.57% in the very valid category. The media expert validation results obtained a score of 82.22% in the valid category. The linguist validation results obtained a score of 92.5% with a very valid category. The teacher response test results obtained a score of 92.5% with a very valid category. The results of the student response test obtained a score of 90.95% with a very valid category. Based on these results, the Magic Learning Box (Kobela) learning media was declared suitable for use in the learning process. 2) The effectiveness of the Magic Learning Box (Kobela) learning media in increasing the learning interest of Class IV students at SD Negeri 101961 Timbang Deli was stated to be effective in the learning process and can improve students' reading skills.